2020
DOI: 10.1002/jper.20-0295
|View full text |Cite
|
Sign up to set email alerts
|

Novel and known periodontal pathogens residing in gingival crevicular fluid are associated with rheumatoid arthritis

Abstract: Background: Periodontitis is a suspected environmental risk factor for the development of rheumatoid arthritis (RA). However, correlation mechanisms between the two pathologies remain elusive. This study examined potential correlations between detached subgingival bacteria collected in gingival crevicular fluid (GCF) and RA parameters. Methods: RA patients (n = 52, F:M = 40:12), patients with Behcet's disease (BD, n = 40, F:M = 29:11) as another systemic inflammatory disease were studied along with a systemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…A study from the USA reported a positive relationship between P. gingivalis and periodontal diseases ( Mikuls et al., 2012 ). Also, it revealed that P. gingivalis was the most potent predictor of periodontal diseases among adolescents ( Janssen et al., 2015 ; Manoil et al., 2021 ). The importance of our findings of a higher correlation rate of P. gingivalis in RA compared to healthy tissue is uncertain ( Rodriguez et al., 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…A study from the USA reported a positive relationship between P. gingivalis and periodontal diseases ( Mikuls et al., 2012 ). Also, it revealed that P. gingivalis was the most potent predictor of periodontal diseases among adolescents ( Janssen et al., 2015 ; Manoil et al., 2021 ). The importance of our findings of a higher correlation rate of P. gingivalis in RA compared to healthy tissue is uncertain ( Rodriguez et al., 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the tongue-coating type is closely related to RA activity. Previous studies found that the abundance of Actinomyces and Campylobacter in RA patients was significantly higher than that in healthy controls [ 48 , 49 ]. The aforementioned results suggest that Leptotrichia and Campylobacter could be promising biomarkers of yellow coating and are related to the hot syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows typical photomicrographs of two Veillonella species as observed under differential interference contrast (DIC) and epifluorescence microscopy using fluorescent probes targeting the 16S rRNA. The genus stems from the Order Veillonellales that also includes the genera Dialister, Megasphaera , and Anaeroglobus , which have been recently proposed as putative periodontopathogens [ 42 , 43 ]. Recognized human oral Veillonella species include: Veillonella parvula, Veillonella dispar, V. atypica, Veillonella denticariosi (reportedly enriched in carious dentine), Veillonella rogosae (reportedly enriched in caries-free individuals), Veillonella tobetsuensis (often isolated form the tongue), Veillonella infantium and Veillonella nakazawae [ 32 , 33 , 38 ].…”
Section: Taxonomymentioning
confidence: 99%